Body mass index trajectories in childhood and incidence rates of type 2 diabetes and coronary heart disease in adulthood: A cohort study. (September 2022) - Blond, Kim; Vistisen, Dorte; Aarestrup, Julie; Bjerregaard, Lise G.; Hudda, Mohammed T.; Tjønneland, Anne; Allin, Kristine H.; Jørgensen, Marit E.; Jensen, Britt W.; Baker, Jennifer L.
Abstract: Aims: We examined associations between five body mass index (BMI) trajectories from ages 6–15 years and register-based adult-onset type 2 diabetes mellitus (T2D) and coronary heart disease (CHD) with and without adjustment for adult BMI. Methods: Child and adult BMI came from two Danish cohorts and 13, 205 and 13, 438 individuals were included in T2D and CHD analyses, respectively. Trajectories were estimated by latent class modelling. Incidence rate ratios (IRRs) were estimated with Poisson regression. Results: In models without adult BMI, compared to the lowest trajectory, among men the T2D IRRs were 0.92 (95 %CI:0.77–1.09) for the second lowest trajectory and 1.51 (95 %CI:0.71–3.20) for the highest trajectory. The corresponding IRRs in women were 0.92 (95 %CI:0.74–1.16) and 3.58 (95 %CI:2.30–5.57). In models including adult BMI, compared to the lowest trajectory, T2D IRRs in men were 0.57 (95 %CI:0.47–0.68) for the second lowest trajectory and 0.26 (95 %CI:0.12–0.56) for the highest trajectory. The corresponding IRRs in women were 0.60 (95 %CI:0.48–0.75) and 0.59 (95 %CI:0.36–0.96). The associations were similar in direction, but not statistically significant, for CHD. Conclusions: Incidence rates of adult-onset T2D were greater for a high child BMI trajectory than a low child BMI trajectory, but not in models that included adult BMI.